Impact of Three Consecutive Days of Endurance Training Under Hypoxia on Muscle Damage and Inflammatory Responses - Sumi, Daichi; Yamaguchi, Keiichi; Goto, Kazushige (Frontiers in Sports and Active Living, 2021)
Purpose: The purpose of this study was to determine the effect of 3 consecutive days of endurance training under hypoxia on muscle damage, inflammation, and performance responses. Methods: Nine active healthy males completed two trials in different periods, consisting of either 3 consecutive days of endurance training under hypoxia [fraction of inspired oxygen (Fio2): 14.5%, HYP] or normoxia (Fio2: 20.9%, NOR). They performed daily 90-min sessions of endurance training consisting of high-intensity endurance interval pedaling [10 × 4-min pedaling at 80% of maximal oxygen uptake (V˙o2max) with 2 min of active rest at 30% of V˙o2max] followed by 30-min continuous pedaling at 60% of V˙o2max during 3 consecutive days (days 1–3). Venous blood sample, muscular performance of lower limb, and score of subjective feelings were determined every morning (days 1–4) to evaluate muscle damage and inflammation. On day 4, subjects performed an incremental exercise test (IET) to evaluate the performance response. Results: Pedaling workload during daily endurance training was significantly lower in the HYP trial (interval exercise: 166 ± 4 W) than in the NOR trial (194 ± 8 W; P < 0.0001). Serum creatine kinase (CK) and high-sensitivity C-reactive protein (hsCRP) concentrations did not significantly change during days 1–4 in either trial. Maximal voluntary contraction (MVC) of knee extension (P < 0.0001) and drop jump (DJ) index (P = 0.004) were significantly decreased with training in both trials, with no significant difference between trials. The muscle soreness and fatigue scores significantly increased in both trials (P < 0.0001). However, the HYP trial showed a significantly lower score of fatigue on day 4 compared with the NOR trial (P = 0.004). Maximal aerobic power output during IET on day 4 did not significantly differ between trials. Conclusion: Three consecutive days of endurance training under hypoxia induced comparable levels of muscle damage, inflammation, and performance responses compared with the same training under normoxia.